Challenges and Opportunities of Artificial Intelligence on Composite Material Engineering - Umeliwu, Onyeka Augustine; Samuel, Bassey Okon (Journal of Sustainable Materials Processing and Management, 2024)
This paper explores the transformative potential of Artificial Intelligence (AI) in composite material engineering, addressing the challenges and opportunities associated with integrating AI technologies into this field. Despite the significant advancements in AI, its application in composite material engineering faces hurdles such as data acquisition and preprocessing, model interpretability, and computational resource limitations. This paper outlines strategies to overcome these challenges, including enhancing data acquisition techniques, developing interpretable AI models, and investing in computational infrastructure. Additionally, we emphasize the importance of interdisciplinary education, ethical governance, and regulatory frameworks to ensure the responsible use of AI. The implications of AI for the future of composite material engineering are profound, with the potential to revolutionize material design, optimization, and manufacturing processes, leading to breakthroughs in performance, efficiency, and sustainability. By fostering collaboration, strategic planning, and innovation, this paper aims to chart a path forward for leveraging AI to drive advancements in composite material engineering that benefit society and promote environmental sustainability.